A Development of Learning Achievement in Thai Language Subjects on Royalty Terminology of Grade 10 Students using Exercises with TAI Techniques - Waikerd, Sukanya; Pengpoom, Brapaas (Ratchaphruek Journal, 2024)
This research aimed to study the development of learning achievement in Thai language subjects on royalty terminology of grade 10 students using exercises with TAI techniques. The objectives were: 1) To create and test the efficiency of exercises according to the standard criteria 80/80; 2) To compare the learning achievement before and after studying; and 3) To study the students’ satisfaction. The sample group includes 40 grade 10 students, semester 2, academic year 2023, Lomsakwittayakhom School, under the jurisdiction of the Phetchabun Secondary Educational Service Area Office, from cluster random sampling using the classroom as a random unit. The research tools used were lesson plans, exercises, academic achievement test, and student satisfaction questionnaire. Statistics used in data analysis were mean, standard deviation, and Dependent t-test. The research results found that 1) the efficiency of the exercises had an efficiency of 84.40/84.89, which is higher than the set standard, 2) the achievement of grade 10 students pre- and post-learning tests showed average scores of 18.38 and 24.25 respectively, with a statistical significance of .05, and 3) grade 10 students expressed the highest overall satisfaction ( = 4.52, S.D. = 0.61)